2013
DOI: 10.1371/journal.pone.0073562
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat Poisoning Induces TNF-α-Dependent iNOS/NO Mediated Hyporesponsiveness of the Aorta to Vasoconstrictors in Rats

Abstract: Paraquat is a toxic herbicide that may induce acute lung injury, circulatory failure and death. The present work aimed at investigating whether there is systemic inflammation and vascular dysfunction after paraquat exposure and whether these parameters were related. There was neutrophilia and accumulation of neutrophils in lung and bronchoalveolar lavage of animals given paraquat. This was associated with an increase in serum levels of TNF-α. In rats given paraquat, the relaxant response of aortic rings to ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 41 publications
4
10
0
Order By: Relevance
“…By showing restoration of lymphatic contraction frequency in TNF-α-treated vessels upon selective inhibition of iNOS with 1400W, our findings provide a convincing indication of the pre-eminent role of iNOS in the TNF-α-induced decrease in pumping. These data are also consistent with studies demonstrating iNOS-dependent impairment of arterial contractility by TNF-α [2,27]. Involvement of iNOS was further strengthened by qPCR data showing that the significant up-regulation of iNOS mRNA expression in lymphatic vessels treated with TNF-α was reversed in the presence of PDTC.…”
Section: Discussionsupporting
confidence: 90%
“…By showing restoration of lymphatic contraction frequency in TNF-α-treated vessels upon selective inhibition of iNOS with 1400W, our findings provide a convincing indication of the pre-eminent role of iNOS in the TNF-α-induced decrease in pumping. These data are also consistent with studies demonstrating iNOS-dependent impairment of arterial contractility by TNF-α [2,27]. Involvement of iNOS was further strengthened by qPCR data showing that the significant up-regulation of iNOS mRNA expression in lymphatic vessels treated with TNF-α was reversed in the presence of PDTC.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the acute exposure to paraquat (20 mg/kg, i.p.) produced a marked increase of neutrophil influx to the broncoalveolar lavage of mice, and this parameter was reduced by TNF-α inhibition [59]. In the present study, the repeated i.p.…”
Section: Discussionsupporting
confidence: 52%
“…Several pathways were clarified as pathways of oxidative injuries by PQ including: reduction of PQ by NADPH-cytochrome P450 reeducates and a subsequent redox cycle, inhibition of mitochondrial electron transport chain, and interaction with nitric oxide syntheses, NADPH oxidase and xanthine oxidase (Ranjbar et al, 2002). Another report showed that PQ enhanced expression of iNOS in aortic endothelial cells and consequently increased the NO production leading to the decreased responsiveness of aortas to vasoconstrictors (Aires et al, 2013).…”
Section: Discussionmentioning
confidence: 99%